Effect of aspect ratio with angle of attack of an oscillating hypersonic delta wing with straight leading edges - Crasta, Asha; Khan, Sher Afghan (IMRF Journals, 2015)
The present study focuses attention on the effect of Aspect ratio of the wing on roll damping moment derivative at various angles of attack and Mach number has been studied. It is found that rolling moment derivative increases with aspect ratio as well as with the angle of attack as the rolling moment derivative is linear function of aspect ratio as well as the angle of attack. It is also seen that with the increase in the aspect ratio, roll damping derivatives decreases with increase in Mach number initially and then confirms the Mach number independence principle for large Mach numbers in the hyper-sonic flow regime. The Present theory is valid only when the shock wave is attached with the wing leading edge, for detached shock case the present theory is no more valid and also the flow will be sub-sonic locally leading to flow separation and finally tremendous deceleration in the flow. Also, the effects of wave reflection and viscosity have not been considered in the present study. Results have been obtained for hyper-sonic flow of perfect gases over a wide range of angle of attack, the Mach number, and the aspect ratio.